Eight‐Electron Redox Cyclohexanehexone Anode for High‐Rate High‐Capacity Lithium Storage (Adv. Energy Mater. 30/2022). Issue 30 (11th August 2022) - Li, Sha; Lin, Jiande; Zhang, Yimiao; Zhang, Shilin; Jiang, Tao; Hu, Zhongli; Liu, Junjie; Wu, De‐Yin; Zhang, Li; Tian, Zhongqun
Abstract : Lithium‐Ion Batteries In article number 2201347, De‐Yin Wu, Li Zhang and co‐workers show that cyclohexanehexone (C6 O6 ) is an ultra‐high capacity and high‐rate anode material for lithium‐ion batteries. Experimental characterization combined with first‐principles calculations elucidate that the CO bonds in C6 O6 can be lithiated to Li + enolate (Li6 C6 O6 ) through a reversible six‐Li‐ion electrochemical process and further converted to Li8 C6 O6 dimers via a reversible two‐electron pseudocapacitive Li + intercalation reaction.